Annelida, Hirudinida, Stibarobdella moorei (Oka, 1910): new distribution and host records. - Wunderlich, Alison Carlos; Gadig, Otto Bismarck Fazzano [UNESP]; Vaske Junior, Teodoro; Pinheiro, Marcelo Antonio Amaro (My University, 2011)
The present report is the northernmost capture of the piscicolid leech Stibarobdella moorei in the western South Atlantic Ocean. This is also the first time S. moorei is found associated to a batoid fish in the Brazilian coast, the eyespot skate Atlantoraja cyclophora. Stibarobdella moorei was found fixed in the dorsal side of a male eyespot skate, caught by bottom trawl around of the São Paulo coast, southeastern Brazil. A brief description of the morphology of the parasite and a discussion on the taxonomic status of the S. moorei are presented.